Subtilase cytotoxin produced by locus of enterocyte effacement‐negative Shiga‐toxigenic Escherichia coli induces stress granule formation. (21st February 2016) - Tsutsuki, Hiroyasu; Yahiro, Kinnosuke; Ogura, Kohei; Ichimura, Kimitoshi; Iyoda, Sunao; Ohnishi, Makoto; Nagasawa, Sayaka; Seto, Kazuko; Moss, Joel; Noda, Masatoshi
Summary: Subtilase cytotoxin (SubAB) is mainly produced by locus of enterocyte effacement (LEE)‐negative strains of Shiga‐toxigenic Escherichia coli (STEC). SubAB cleaves an endoplasmic reticulum (ER) chaperone, BiP/Grp78, leading to induction of ER stress. This stress causes activation of ER stress sensor proteins and induction of caspase‐dependent apoptosis. We found that SubAB induces stress granules (SG) in various cells. Aim of this study was to explore the mechanism by which SubAB induced SG formation. Here, we show that SubAB‐induced SG formation is regulated by activation of double‐stranded RNA‐activated protein kinase (PKR)‐like endoplasmic reticulum kinase (PERK). The culture supernatant of STEC O113:H21 dramatically induced SG in Caco2 cells, although subAB knockout STEC O113:H21 culture supernatant did not. Treatment with phorbol 12‐myristate 13‐acetate (PMA), a protein kinase C (PKC) activator, and lysosomal inhibitors, NH4 Cl and chloroquine, suppressed SubAB‐induced SG formation, which was enhanced by PKC and PKD inhibitors. SubAB attenuated the level of PKD1 phosphorylation. Depletion of PKCδ and PKD1 by siRNA promoted SG formation in response to SubAB. Furthermore, death‐associated protein 1 (DAP1) knockdown increased basal phospho‐PKD1(S916) and suppressed SG formation by SubAB. However, SG formation by an ER stress inducer, Thapsigargin, was not inhibited in PMA‐treated cells. Our findings show that SubAB‐induced SG formation is regulated by the PERK/DAP1 signalling pathway, which may be modulated by PKCδ/PKD1, and different from the signal transduction pathway that results in Thapsigargin‐induced SG formation.